Travel Package Recommendation System Using Collaborative Filtering Method at Loka Travel - Iswanto, Muhammad Edi; Rachman, Andi Nur; Noorsyabani, Fauzi (Deparment Information System, Siliwangi University, 2025)
The rapid development of information technology drives the need for a system that can help tourists in determining the choice of tourist destinations that suit their preferences. The Loka Travel application was developed as a web-based platform that provides various tour packages and is equipped with a recommendation system to suggest relevant destinations for users. This study aims to design and implement a tour package recommendation system using the Collaborative Filtering method with a memory-based approach. This method works by calculating the similarity between users based on their rating or booking history for tour packages, allowing the system to suggest packages that are preferred by other users who have similar preferences. The cosine similarity algorithm is used in the process of calculating the similarity between users, with interaction data obtained from booking and payment activities in the application. The implementation of this system is carried out using the Laravel framework and MySQL database. The results of the system test show that the system is able to provide recommendations with an accuracy level of 80.63%, based on the calculation of Mean Absolute Error (MAE). Thus, this system can help users find suitable tourist destinations and improve their experience in using the Loka Travel application.